Structural Analysis of the Synthetic Duffy Binding Protein (DBP) Antigen DEKnull Relevant for Plasmodium vivax Malaria Vaccine Design - Chen, Edwin; Salinas, Nichole D.; Ntumngia, Francis B.; Adams, John H.; Tolia, Niraj H. (PLOS Neglected Tropical Diseases, 2015)
Author Summary Plasmodium vivax is an oft neglected causative agent of human malaria. It inflicts tremendous burdens on public health infrastructures and causes significant detrimental effects on socio-economic growth throughout the world. P. vivax Duffy Binding Protein (DBP) is a surface protein that the parasite uses to invade host red blood cells and is a leading vaccine candidate. The variable nature of DBP poses unique challenges in creating an all-encompassing generalized vaccine. One method to circumvent this problem is to synthetically engineer a single artificial protein antigen that has reduced variability while maintaining conserved protective motifs to elicit strain-transcending protection. This synthetic antigen is termed DEKnull. Here, we provide structural and biochemical evidence that DEKnull was successfully engineered to eliminate polymorphic epitopes while retaining the overall fold of the protein, including conserved conformational protective epitopes. Our work presents validation for an improved iteration of the DBP P. vivax vaccine candidate, and provides evidence that protein engineering is successful in countering DBP polymorphisms. In doing so, we also lay down the foundation that engineering synthetic antigens is a viable approach and should be considered in future vaccine designs for pathogens.